PENGARUH SERVICE QUALITY DAN PRICE TERHADAP REPURCHASE INTENTION DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA KONSUMEN E-COMMERCE ELEVENIA.CO.ID DI KOTA SEMARANG - Abigail Alda Widyartini; Dinalestari Purbawati (Universitas Diponegoro, 2019)
The increasingly fierce competition between e-commerce makes the company need to increase the interest in repurchasing its consumers, so they can survive and continue to get profits. This research was conducted with the aim of examining the effect of service quality and price on repurchasing interest through customer satisfaction as an intervening variable. This research is quantitative research that uses explanatory type. Sampling technique uses non probability sampling and purposive sampling approach. Where the population is all Elevenia consumers in Semarang, while the sample is 100 Elevenia consumers with certain criteria carried out. Data collection techniques using google form and interviews. The analysis used in this study is linear regression analysis using SPSS 21.0 for Windows software and mediation test (sobel test) to test the mediating effect of intervening variables. The results of this study indicate that service quality and price have a partial and simultaneous effect on customer satisfaction, where when together price has the greatest influence on customer satisfaction. Based on the mediation test using sobel test, the customer satisfaction variable can mediate the effect of service quality on e-repurchse intention insignificantly and can be said as a full mediated variable, as well as the variable customer satisfaction can mediate the influence the price of repurchase intention is not significantly significant and can be said to be a full mediating variable. Based on the results of research Elevenia can increase consumers' repurchasing interest by increasing service quality through better website design, responsiveness in responding to consumer complaints, and fast and good refund services. In addition Elevenia also needs to set prices and discounts that are able to compete with other e-commerce. so that it will increase customer satisfaction, which in turn increases consumer repurchase interest.